The Iranian Government’s Approach towards the Use of Hijab - Faraz, Sara Javadi (2008)
This study has considered the clothing culture of Iranian female and through the first part it will explain the life line of hijab and any possible connection between this Islamic symbol and Iranian dressing culture. In case of declaring the government roles in dressing culture, a considerable attention was paid to the history of Iranian monarchy from Achaemenid up to Qajar and Pahlavi. During the research, the female’s dressing, position in monarchy, aristocracy and society, invading Iran by Islam, adapting and converting the Islamic culture to the Iranian version, were all described in details. The second part of this study is more focused on political aspect of hijab, the history of feminism, the debate about dress code, motherhood and morality, modernization, pre-Islamic revolution atmosphere, Reza Shah Pahlavi’s compulsory unveiling and inspiration of global modernization. The last part of this study is particularly dealing with Islamic revolution and post-revolution era when the hijab suddenly became a matter of state’s concern and women were forced again to cover themselves in public. The study also points out that Iran always understood that clothing is a powerful manifestation of political thought and in turn are evidence that the nation adhere to state ideology. At the end the researcher explains her points of view and emphasises on political perspective of hijab through the conclusion. The main methodological approach of this study is content analysis of documents, books, articles and other materials which conclude the fact that the governments and states attends to instructing the people’s privacy and establishing codes for everything even dressing is a dedication of state’s interference. The researcher has no doubt and proves that although the Iranian dressing culture might look similar to the hijab, there is no evidence of existing a clothing code of conduct in history which could be referred to hijab or any other Islamic symbol of female appearance.